ASSESSING MEANDER BELT WIDTH OF BHAGIRATHI-JALANGI RIVER SYSTEM IN LOWER GANGA DELTA, INDIA - Aznarul ISLAM; Balai CHANDRA DAS; Nishith KUMAR MAJI; Suman DEB BARMAN (European Journal of Geography)
The present work is an attempt to assess the meander belt width of the river Bhagirathi (frequently oscillating) and river Jalangi (relatively stable) in West Bengal, India based on geospatial data and field data (lithological composition and flow characteristics). Belt width has been computed using four major considerations in increasing order of scale- (i) individual loops of the present channel (MBw1), (ii) maximum loop width of the present channel (MBw2), (iii)palaeo channel characteristics identified through normalized difference water index and pixel-based classification coupled with field observation (MBw3) and(iv) future channel based on the factor of safety which is a space-time averaged safe belt width (MBw4). The study found MBw4 of 11.76 km for Bhagirathi and6.64 km for Jalangi considering the 100-year factor of safety. The higher meanderbelt width of Bhagirathi in comparison to Jalangi was found to be correlated with higher monsoon discharge, bed slope, stream power, shear stress, suspended surface sediment concentration, D50, and lower relative bed stability.